List Steganography Based On Syllable Patterns - David Martin; Ari Moesriami Barmawi (eProceedings of Engineering, 2015)
Abstract—List-based steganography or Listega is a steganography methodology with noiseless steganography paradigm, or Nostega. In this methodology, a message is embedded in the first characters of list items to create a list- cover. Listega uses filtered cover, which contains only the embedded list items. There are some rooms of improvements in Listega due to several problems, i.e. small embedding capacity and embedding failure in using several index of Latin square that it uses as mapping method. The proposed method uses syllable patterns of Indonesian language as a method of embedding message using Employee Birthday List. It also introduces an algorithm to make an unfiltered list-cover, which contains the embedded and non-embedded list items. This algorithm also makes possible to provide a grouping and a degree of sorting of list-covers. Furthermore, the results of the experiments show that the proposed method has higher capacity compares to Listega in filtered cover conditions. The use of unfiltered cover also reduces the suspicion from other parties. Keywords—Listega; Noiseless; steganography; syllable patterns